Health services research as a scientific process: the metamorphosis of an empirical research project from grant proposal to final report. - Luft, H S (1986)
The process of health services research is rarely examined; attention is usually focused on results and policy implications. Large and small decisions made during the execution of a study, however, can have major impacts on its outcomes. This article describes a project that underwent major changes because of problems discovered in the basic data and threats to the valid interpretation of econometric results uncovered by qualitative case studies. Although the combination of difficulties encountered in this project may be unusual, it is likely that many similar problems and opportunities occur in other empirical studies.